PARADIGMA PENGEMBANGAN BIMBINGAN PENYULUHAN ISLAM PERSPEKTIF DAKWAH - Muhamad Rifa'i Subhi; Andar Ifzatul Nurlatifah; Rahmat Fawzy (Jurnal Bimbingan Penyuluhan Islam, 2023)
This study aims to describe the paradigm of developing Islamic counseling guidance in the perspective of da'wah. Islamic Counseling Guidance is a process of changing behavior that is carried out through the dissemination of information, communication, motivation, counseling, education, facilitation and advocacy both orally, in writing and in practice in order to develop knowledge, attitudes and behavior of target community groups so that they know, are motivated and are able to understand, carry out the teachings of Islam correctly while at the same time have concern and active participation in the development of the social or religious field by using the language or teachings of the religion of Islam. The type of research used is library research with a descriptive qualitative research design, in order to obtain comprehensive research results regarding Islamic counseling guidance. The results of the study show that the paradigm of developing Islamic counseling guidance in the perspective of da'wah can be identified based on understanding, duties and functions, materials, strategies and methods, profession, and competency standards of Islamic religious instructors. These six findings can be used as a basis for Islamic religious instructors in carrying out their professional duties, so as to create optimal Islamic counseling guidance services.